2016
DOI: 10.1016/j.ijscr.2016.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic extra-abdominal suturing technique for the repair of Larrey’s diaphragmatic hernia using the port closure needle (Endo Close ® ): A case report

Abstract: HighlightsLarrey’s diaphragmatic hernia is relatively uncommon.It is difficult to suture the hernial orifice laparoscopically.Extra-abdominal suturing technique using Endo Close® may be useful in terms of secure suture and easy tying.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…Only 4% of the reported cases are bilateral. The defect results from a fusion failure of the diaphragm with the costal arches [2][3][4][5][6]. Sanford et al reported that the average length of the diaphragmatic defect in the greatest dimension is 7.5 cm [6].…”
Section: Discussionmentioning
confidence: 99%
“…Only 4% of the reported cases are bilateral. The defect results from a fusion failure of the diaphragm with the costal arches [2][3][4][5][6]. Sanford et al reported that the average length of the diaphragmatic defect in the greatest dimension is 7.5 cm [6].…”
Section: Discussionmentioning
confidence: 99%
“…laparoscopic or thoracoscopic approach. The well-known advantages of the minimally invasive treatment, including the faster postoperative recovery, as well as the shorter hospitalization period and minimal scarring, urged an increased number of surgeons to treat the patients in this manner in the last several years [1,14]. The robotic surgery, whether transabdominal or transthoracic, represents another technological progress with well-recognized advantages: ergonomics, preciseness of instruments, as well as easy operation in narrow spaces [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…The robotic surgery, whether transabdominal or transthoracic, represents another technological progress with well-recognized advantages: ergonomics, preciseness of instruments, as well as easy operation in narrow spaces [15,16]. With regard to the treatment with a small-diameter hernia opening (less than 16 cm 2 ), it is possible to perform a primary suture, while in larger defects (larger than 20-30 cm 2 ), the plastics of the diaphragm opening is induced with the help of various kinds of meshes, to avoid tension [14]. The data from the literature indicate that polypropylene meshes are mainly applied, but the possibility of using other types of meshes has not been excluded [17].…”
Section: Discussionmentioning
confidence: 99%
“…Nonabsorbable 00 sutures are preferred for primary repair. In the transfacial extracorporeal technique, Endo Close® is inserted into the abdomen through mini incisions (described by Yamamato) [28], and the sutures that were previously sent into the abdomen are held one by one and pulled out of the abdomen and ligated to the hernia defect. The sutures are passed one by one 1 or 2 cm apart and are thrown to cover the cranial and caudal borders of the hernia defect.…”
Section: Surgical Indicationmentioning
confidence: 99%